PENGARUH KEPEMIMPINAN TRANSFORMASIONALONAL KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU PADA SEKOLAH BERBASIS AGAMA DI BALANGAN(STUDI KASUS PADA SMAN 2 HALONG) - Miranti Miranti (CV. ADIBA ASIHA AMIRA, 2023)
Principal leadership is a person's ability in the process of influencing, guiding, encouraging, moving and directing others in terms of learning and can run effectively. Work motivation is something that creates enthusiasm or encouragement to work. Teacher performance is also a factor that determines the quality or not of a school institution. From the explanation above, the author writes the formulation of the problem, namely whether there is an influence of transformational leadership of school principals and work motivation on teacher performance in religion-based schools at SMAN 2 Halong. The purpose of this study was to determine the effect of the principal's transformational leadership and work motivation on teacher performance in a religion-based school at SMAN 2 Halong. This type of research uses a quantitative descriptive approach. The purpose of quantitative research is to develop and use mathematical models, theories and hypotheses related to natural phenomena. As for the population in this study, all teachers were used, and the sample used in this study was a saturated sample, namely all teachers at SMAN 2 Halong. The data analysis technique used to test the hypothesis is simple regression analysis with multiple regression, t test and F test. The results show that there is an effect of transformational leadership on religion-based schools at SMAN 2 Halong, that the results of the X1 variable test on Y show the result t count is 2.047 > t table 1.66 with a significant level of 0.043 <0.05, Transformational Leadership (X1) has a partial effect on religion-based schools (Y).